Accumulation, depuration and effects of copper on the growth, feeding rate, reproduction and histology of the golden apple snail Pomacea canaliculata LAMARCK - Peña, Silvia C. (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliiman, 2007)
Golden apple snail, Pomacea canaliculata Lamarck, an agricultural pest in Asia, was exposed to 5 nominal copper concentrations to test if it could be a metal biomonitor. To have a more comprehensive knowledge on the over-all effect of copper (Cu+2) on P. canaliculata, the feeding and growth rates, reproduction, accumulation and depuration patterns and histology were studied.